The association between household food security, dietary diversity, and stunting among toddlers in West Bandung Regency - Yasmin Putri Prasanti; Asti Dewi Rahayu F; Widya Astuti; Ahdiyatul Fauza (AcTion: Aceh Nutrition Journal, 2026)
Stunting remains a major public health issue in Indonesia, particularly in rural areas such as Cihanjuang Rahayu Village, West Bandung Regency, where a high prevalence of stunting coincides with a declining food-security index. This study aimed to analyze the relationship between household food security, dietary diversity, and the incidence of stunting in toddlers aged 24–59 months. A cross-sectional design was employed, involving 94 toddlers selected through proportional stratified random sampling method. Toddler height was measured using a stature meter and analyzed using WHO Anthro software. Household food security was assessed using the Household Food Insecurity Access Scale (HFIAS), and dietary diversity was measured using a 24-hour recall and the Household Dietary Diversity Score (HDDS). Logistic regression analysis (SPSS v29) was conducted to control for potential confounders. Results: The prevalence of stunting in the study area was 30.9%. Food insecurity was significantly associated with stunting (p = 0.022; OR = 3.130; 95% CI: 1.182–8.284), as was low dietary diversity (p = 0.009; OR = 5.881; 95% CI: 1.564–22.107). In conclusion, these findings highlight the importance of improving household food access and dietary quality through targeted family based nutrition education and community-level interventions to effectively reduce the prevalence of stunting.